Profil Literasi Sains Siswa di SMP Negeri Perkotaan dan Pedesaan : Profile of Student's Scientific Literacy in Urban and Rural State Middle Schools - Shofiyah, Noly; Faizah, Nova Auliyatul (Universitas Muhammadiyah Sidoarjo, 2018)
This study purposes to describe the profile of scientific literacy of students in urban and rural State Junior High Schools. In urban areas, this study was conducted in SMP Negeri 3 Sidoarjo and in rural areas, the study was in SMP Negeri 2 Jabon. The subjects of this study were 2 students of VIII grade from each SMP Negeri 3 Sidoarjo and SMP Negeri 2 Jabon. In this study using qualitative methods, data was collected using tests, interviews, and observations. This scientific literacy test was adapted from the 2013 Pan-Canadian Assessment Program (PCAP) because students were in VIII grade. The results showed that students in urban schools had scientific literacy on problem solving indicators reaching levels 4 and 3, scientific inquiry indicators reached levels 3 and 2, and indicators of scientific reasoning reached level 3. Meanwhile, students in rural schools had scientific literacy at level 2 and 1 on indicators of problem solving, scientific inquiry indicators reach level 2 and 1, and scientific reasoning reaches level 3 and 2.